The Mosques of Egypt from 21 H. (641) to 1365 H. (1946): Volume II (Egypt Ministry of Waqfs, 1949)
Being a Series of Views in Color and Monochrome of the Principal Mosques of Egypt with a Brief Note on Each Monument, Describing its History and Architectural Features, Accompanied by Detailed Plans and Maps.
"Index to Mohammedan monuments in Cairo" (11, 14, 13 p., 2 fold. col. maps) published in 1951 by the Survey of Egypt, inserted in pocket, vol. 1.
Four unnumbered pages with Introduction and Preface dated 4th June 1954 inserted to replace matter between page D and page 2. Original text on p. 2 covered by mounted blank label.
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; Mosques -- Egypt; General